Driving forces of economic systems in the conditions of the formation of human environmental security (Economics and region, 2023)
The article reviews the history of economic teachings, their methodological principles in the context of the formation of ecological and economic theories and environmental economics and the global ecological and economic system. The special value of certain economic theories, economic schools and analysis in the economy is determined by the fact that different peoples and countries live in different economic times, and certain economic time periods have different regional institutional features. The need for regulatory influence on the economic system, with the aim of preventing the processes of natural and economic entropy, has been studied. It is emphasized that the need for the formation of world and state economic systems, incentives and sanctions, and ecological and economic standards and carbon tax. It was determined that the most rationally absorbs the idea of sustainable development and forms the mechanism of institutional balance and compromises, the institutional environmental economic system.
Keywords: economic theory; environmental economics; ecological and economic norms; economic present; institutional balance